"Christian But Not Religious": Being Church as Christian Hardcore Punk. (23rd August 2017) - McDowell, Amy D
Abstract: Studies show that Christian youth in the United States are dropping out of church because they are disillusioned with organized religion, not because they have lost faith in God. Scholars propose that these youth are approaching spirituality in individualistic ways and finding God on their own instead of in buildings designated as church. This research on Christian Hardcore punk rock problematizes the idea that the youth who leave conventional churches necessarily turn into spiritual individualists. Drawing on qualitative research at live music shows in secular venues, Christian rock festivals, and a subcultural ministries conference, this article shows that some youth are collectively reimagining and being church in and through music that both opposes mainstream Christianity and blurs religious and nonreligious boundaries. This article also offers a new approach to the study of youth and religious participation in an age in which mainstream religious practices are far less authoritative and meaningful to youth than these alternative cultural expressions are.